Paul as a Problem in History and Culture : the Apostle and His Critics through the Centuries - Gray, Patrick, 1970- (Grand Rapids, MI : Baker Academic, 2016)
As one of the most significant figures in the history of Western civilization, the apostle Paul has influenced and inspired countless individuals and institutions. But for some, he holds a controversial place in Christianity. This engaging book explores why many people have been wary of Paul and what their criticisms reveal about the church and the broader culture. Patrick Gray brings intellectual and cultural history into conversation with study of the New Testament, providing a balanced account and assessment of widespread antipathy to Paul and exploring what the controversy tells us about ourselves.
Introduction: A thorn in the flesh -- Part 1. Anti-Paulinism through the centuries : -- 1. The first hundred years: the problem of Paul in the New Testament -- 2. The premodern era: the early church, late antiquity, and the Middle Ages -- 3. The Enlightenment and beyond: Jesus, Paul, and the rise of modern biblical scholarship -- 4. The nineteenth century: Paul's cultured despisers -- 5. Yesterday and today: Jesus versus Paul in the public square -- Part 2. Anti-Pauline contexts, subtexts, and pretexts : -- 6. In the tents of Shem: Paul among Jews and Muslims -- 7. Jesus versus Paul: spiritual but not religious? -- 8. A world without Paul?: Christian history in counterfactual perspective -- 9. Not by Paul alone: other 'founders' of Christianity -- 10. From Jesus to Paul: an experiment in comparative religion -- Conclusion: What we talk about when we talk about Paul.
Includes bibliographical references (pages 211-244) and index.
Keywords: Paul, -- the Apostle, Saint; Paul and Controversial History -- Apostle and Critics through Centuries